Oral health knowledge, attitudes, and practices among university students in Bangladesh: a cross-sectional study - Md. Nazrul Islam; Md Sirajul Islam Pial; Mohammad Abdulla Al Noman; Felix Kwashie Madilo; M. M. Mehedi Hasan; Sunjida Munmun; Tamanna Hassan; Carmilla Shaltel Naa Angerley Mensah; Nitai Roy (Discover Public Health)
Abstract Objectives Oral health is an important aspect of overall well-being, but little is known about oral health behaviors and contributing factors among Bangladeshi university students. The purpose of this study is to better understand the oral health knowledge, attitude, and practices of students and the factors that influence them. Methods Data were collected using a validated structured questionnaire that asked about oral health and socio-demographic variables. The non-probability convenience sampling method was used to recruit participants, selecting individuals based on their availability and willingness to participate. The study was conducted between January and March 2023 with 1,098 university students from three public universities. Multiple logistic regression was used to assess the predictors of students' oral health outcomes with respect to demographic characteristics. Results Of the participants, 58.6% were between the ages of 21 and 24, 55.9% were men, and 58.2% were from rural areas. Females consistently demonstrated stronger oral health knowledge and practices relative to males. Parental education, particularly mother education, emerged as a significant predictor of knowledge and practices; lower mother education levels were consistently related with poorer results, whereas lower father education levels were consistently connected with better odds. Family income also had an impact, with participants from low-income households having a reduced likelihood of strong knowledge. Poor attitudes were significantly associated with poor knowledge and practices, emphasizing the need of creating good beliefs of oral health. The university year revealed significant inequalities, with undergraduates, particularly second-year students, being less likely to engage in best practices. Conclusions The results emphasize the substantial disparities in oral health knowledge, attitudes, and practices that are influenced by gender, parental education, and socio-economic status. Tailored interventions, such as integrating oral health education into university curricula, focusing on male students and those from poorer socioeconomic backgrounds, and organizing workshops and awareness campaigns, are essential.